Analysis of the Implementation of Good Governance Principles in the Formation of Laws and Regulations in Indonesia - Kirana Utami, Tanti; St May, Nazwa; Nurajijah, Siti; Al Zaidan, Helmi; Meika Putra Hendrawan, Farrel; Fahril, M. Algi (Indonesian Journal Publisher, 2024)
This study analyzes the implementation of the principles of good governance in the formation of laws and regulations in Indonesia. While principles such as transparency, participation, accountability, and effectiveness are expected to improve the quality of regulation and public trust, the practice still faces various challenges. Overlapping regulations, a lack of substantial public participation, and the accountability of legislative institutions influenced by political interests are the main obstacles. This study uses a normative juridical approach to evaluate the extent to which these principles are applied and their impact on the quality of regulations. The results of the analysis show that the ineffectiveness of the implementation of good governance principles contributes to the low quality of laws and regulations, as well as reduces public trust in the government. Therefore, reforms are needed in the legislative process to ensure that the principles of good governance are effectively integrated, in order to achieve sustainable legal development that is responsive to the needs of society.